The Influence of KPI-Based Performance Assessment System on Employee Motivation and Productivity at PT. Berca Hardiaperkasa Luwuk Central Sulawesi - Juniche Irene Sarapang; Christian August Harold Legoh; Nani Nurcahyani Hi. Yusuf; Wahyudin Rahman (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to analyze the effect of Key Performance Indicator (KPI)-based performance appraisal system, leadership style, and work motivation on employee productivity. The research method used is a quantitative approach with multiple linear regression analysis techniques. The results of the study indicate that simultaneously, the implementation of KPI, leadership style, and work motivation have a significant effect on employee productivity. Partially, the implementation of KPI and leadership style have a positive and significant effect on employee productivity, indicating that an effective KPI system and good leadership can improve individual performance. However, the results of the study also show that work motivation does not have a significant effect on employee productivity, indicating that there are other factors that may play a greater role in improving productivity. The implication of this study is that organizations need to focus more on optimizing the KPI system and developing a leadership style that can support the achievement of employee productivity.